Plant oxylipins: adaptation to environmental stresses and impact on mycotoxin contamination - Di Pasquale, Giovanni; Ottaviani, Letizia; Camardo Leggieri, Marco; Giorni, Paola; Marocco, Adriano; Battilani, Paola; Lanubile, Alessandra (Frontiers in Plant Science, 2026)
Due to increasingly frequent changes in climatic conditions and global warming, plants consistently deal with severe weather events including extreme temperature variations, floods and drought. These abiotic stressors resulting from climate change weaken host crop resistance, making them more exposed to fungal disease insurgences and mycotoxin contamination. Oxylipins are major players in the plant-environment interaction. Their synthesis begins with the oxygenation of polyunsaturated fatty acids by lipoxygenases (LOXs) to generate fatty acid hydroperoxides that in turn are converted into a huge assortment of bioactive compounds by specialized cytochrome P450 enzymes, known as CYP74. In the present review we focus on recent advances concerning oxylipin biosynthesis and the phylogenetic relationships among the main key enzymes of the oxylipin pathway considering five monocot and dicot plant species. Moreover, new information regarding the role of these signaling molecules on the plant physiology in response to abiotic stress and mycotoxin occurrence are provided along with the application of clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR associated (Cas) (CRISPR/Cas)-based tools. Here, we report the intervention of LOX, allene oxide synthase, OPDA reductase, JASMONATE (JA) resistant and JA ZIM domain genes along with the accumulation of JA and its conjugates, 12-OPDA, ketols and green leaf volatiles in response to abiotic stress. The modulation of LOX genes and the production of several fatty acids, oxylipins and sphingolipids is also required against mycotoxin contamination.